(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial Intelligence (AI) is reshaping the way organisations manage their human resources by introducing greater speed, accuracy, and analytical capability into HR decision-making. Activities that were once largely administrative and dependent on manual intervention are increasingly supported by intelligent technologies capable of processing vast amounts of workforce data and generating actionable insights. As a result, Human Resource Management (HRM) is evolving into a strategic function that contributes directly to organisational performance and long-term competitiveness. This paper examines the influence of AI across three core dimensions of the employee lifecycle: recruitment and talent acquisition, performance management, and employee retention. It reviews the growing use of technologies such as Natural Language Processing (NLP), machine learning, intelligent applicant tracking systems, conversational AI, sentiment analysis, and predictive analytics. Drawing upon recent academic literature, industry reports, and organisational case studies, the paper highlights the measurable benefits associated with AI adoption, including shorter recruitment cycles, more objective performance evaluation, improved workforce planning, and stronger employee retention outcomes. The discussion also recognises that the implementation of AI is accompanied by important ethical, legal, and organisational challenges. Issues relating to algorithmic bias, data privacy, transparency, explainability, and employee trust continue to influence the responsible deployment of AI-enabled HR systems. The paper argues that sustainable success depends not on replacing human judgement with intelligent systems but on integrating technological capabilities with ethical governance and professional expertise. It concludes that an augmented model, in which AI enhances rather than replaces human decision-making, offers the most balanced and effective approach for future-ready Human Resource Management.